Evaluation of the influence of UV radiation and sodium hypochlorite on the shelf life of strawberries (Research, Society and Development, 2021)
It is common to combine methods to increase the shelf life of a raw material or product. In this study, we sought to understand the relationship between ultraviolet (UV) radiation and sodium hypochlorite (NaOCl) in attenuating the proliferation of fungus and its deteriorating effect on strawberries. The UV light intensities of 125, 250 and 400 Watts (W) and sodium hypochlorite were tested in concentrations 0.5, 1.0 and 1.5 ppm. The strawberries were sprayed with sodium hypochlorite solutions and then kept for 1 minute in UV light chambers, to then be stored in transparent sealed plastic containers. The strawberry samples with the longest life were those that were sprayed with 0.5 and 1.0 ppm sodium hypochlorite solution combined with exposure to 125 W UV light. These samples had a shelf-life extension of about five days compared to strawberries without any kind of treatment. Thus, it is possible to state that this combination is efficient in cleaning the fruit without causing damage.